Risk Aversion among Poultry Egg Producers in Southwestern Nigeria - Ajetomobi, J.O.; Binuomote, S.O. (International Journal of Poultry Science, 2006)
Attitudes towards risk among poultry producers in Southwestern Nigeria are derived from a survey data in a model of safety – first behaviour. The measurements of behaviour toward risk obtained were explained by a set of socioeconomic and structural characteristics of the farmers. The results showed that feed is the most important determinant of egg output in Southwestern Nigeria. The risk premiums were low, encouraging the use of the feeds under safety-first behaviour. The regression results support the hypothesis that risk- bearing capacity of the poultry farmers can be explained by their socio-economic characteristics. Particularly significant for that purpose were family size of respondents, capacity of deep litter, cost of veterinary services, cost of construction of deep litter and cost of purchase of land.